2017
DOI: 10.1073/pnas.1703998114
|View full text |Cite
|
Sign up to set email alerts
|

Quadrupling efficiency in production of genetically modified pigs through improved oocyte maturation

Abstract: Assisted reproductive technologies in all mammals are critically dependent on the quality of the oocytes used to produce embryos. For reasons not fully clear, oocytes matured in vitro tend to be much less competent to become fertilized, advance to the blastocyst stage, and give rise to live young than their in vivo-produced counterparts, particularly if they are derived from immature females. Here we show that a chemically defined maturation medium supplemented with three cytokines (FGF2, LIF, and IGF1) in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
117
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 79 publications
(86 reference statements)
3
117
3
1
Order By: Relevance
“…One possible reason may be gilt oocyte's smaller size (Pedersen et al., ) or mitochondrial content (Pedersen, Løvendahl, Larsen, Madsen, & Callesen, ). Another explanation could relate to the CCs in gilt oocytes, as adding cytokines during IVM improve CC maturation and embryonic development (Yuan et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason may be gilt oocyte's smaller size (Pedersen et al., ) or mitochondrial content (Pedersen, Løvendahl, Larsen, Madsen, & Callesen, ). Another explanation could relate to the CCs in gilt oocytes, as adding cytokines during IVM improve CC maturation and embryonic development (Yuan et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, results from RT‐PCR analysis showed that activation of the mitogen‐activated protein kinase (MAPK) pathway in cumulus cells seems to have an important role in cumulus expansion and meiotic maturation of porcine COCs. Based on this, Yuan et al () supplemented the maturation medium with three cytokines (FGF2, LIF, and IGF1), named “FLI,” and observed a fourfold increase in the efficiency of piglet production. Supplementation of the IVM medium with FLI enhanced nuclear maturation and led a twofold increase in blastocyst production after IVF.Deep sequencing analysis of IVV or IVC porcine blastocysts identified 1,170 differentially expressed transcripts between these two conditions with 588 of these transcripts exhibiting at least a twofold difference (Bauer et al, ).…”
Section: Transcriptomic and Metabolomic Approaches To Understand Preimentioning
confidence: 99%
“…Based on this, Yuan et al (2017) supplemented the maturation medium with three cytokines (FGF2, LIF, and IGF1), named "FLI," F I G U R E 1 Advancements in in vitro culture system protocols to improve development of porcine embryos. Selection of adequate external conditions and supplementation with amino acids, cytokines, and different small molecules during in vitro maturation (IVM), in vitro fertilization (IVF), and in vitro culture (IVC) improved development of in vitro-produced porcine embryos.…”
Section: Transcriptomic and Metabolomic Approaches To Understand Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Pigs are increasingly being used as an ideal animal model for humans in reproductive medicine research because they share many similarities in the aspects of physiology (aneuploidy rate), developmental timing (oocyte maturation and early embryo development), and genetics with humans (Mordhorst and Prather, 2017). Although many efforts have been made to improve the oocyte maturation in vitro in pigs, its meiotic and developmental capacity is still suboptimal relative to that under the physiological states (Nagai, 2001; Yuan et al, 2017). This may be due to the imperfectness of in vitro culture conditions currently used that cannot achieve the optimal maturational outcomes, and there is inadequate information regarding the unique molecular mechanisms of porcine oocyte meiotic maturation (Sun and Nagai, 2003; Prather et al, 2009).…”
Section: Introductionmentioning
confidence: 99%